Legal Construction of Child and Adolescent Privacy Protection in the Digital Age: The Dilemma between Cyber Protection and Information Access in Schools - Munna, Navis Nailil (Law and Judicial Review, 2025)
Objective: This study aims to analyze the legal construction of child and adolescent privacy protection in Indonesia in the digital age, particularly addressing the dilemma between the need for cybersecurity and the right to access information in schools. Research Design & Methods: This study uses a qualitative method with a normative juridical approach through a literature review of laws, scientific literature, and related legal sources, which are analyzed descriptively and qualitatively to identify normative gaps and provide recommendations for the protection of children's privacy in the digital age. Findings: The findings reveal that Indonesia's legal framework on child privacy protection is still fragmented, with overlapping regulations, a lack of specific norms, and a lack of standard protocols for managing personal data in educational institutions. Compared to the GDPR and COPPA, Indonesian regulations are still less comprehensive, especially in terms of monitoring, law enforcement, and parental consent requirements. Schools face a significant dilemma in balancing cybersecurity measures with ensuring students' rights to access information as part of their learning process. Implications & Recommendations: This study emphasizes the importance of strengthening child privacy regulations in Indonesia through implementing specific norms, data management standards in schools, the principle of Privacy by Design, and increased digital literacy for all stakeholders to create a safe and inclusive digital education ecosystem. Contribution & Value Added: This research strengthens the discourse on child data privacy protection in Indonesia by critically comparing it with international regulations and emphasizing the importance of balancing cybersecurity and the right to information as a legal and educational necessity in the digital age.